Adsorption of cholic acid on silica modified with benzyltrimethylammonium groups - Roik, N.V.; Belyakova, L.A.; Varvarin, A.M. (Functional Materials, 2007)
Chemical fixation of benzyltrimethylammonium groups on vinyl silica surface has been realized using a copolymerization reaction. It has been found that cholic acid is better adsorbed on the modified silica than on choloestyramine. Main paramenters of adsorption - constants of ion exchange, aggregation, and stability - have been calculated, and conclusion about mechanism of cholic acid adsorption on modified silica have been made.